Perspective in Progress of Cardiovascular Gene Therapy - Ryuichi Morishita (Elsevier, 2004)
Recent progress in molecular and cellular biology has developed numerous effective cardiovascular drugs. However, there are still a number of diseases for which no known effective therapy exists, such as peripheral arterial disease, ischemic heart disease, restenosis after angioplasty, vascular bypass graft occlusion, and transplant coronary vasculopathy. Currently, gene therapy is emerging as a potential strategy for the treatment of cardiovascular disease to treat such diseases despite of its limitations. The first human trial in cardiovascular disease was started in 1994 to treat peripheral vascular disease using vascular endothelial growth factor (VEGF). Since then, many different potent angiogenic growth factors have been tested in clinical trials to treat peripheral arterial disease. The results from these clinical trials seem to exceed expectations. Improvement of clinical symptoms in peripheral arterial disease and ischemic heart disease has been reported. In addition, another strategy for combating disease processes, the targeting of transcriptional processes, has been tested in a human trial. Genetically modified vein grafts transfected with decoy against E2F, an essential transcription factor in cell cycle progression, revealed apparent long-term potency in human patients. This review focuses on the future potential of gene therapy for the treatment of cardiovascular disease. Keywords:: cis-element decoy, antisense, angiogenesis, vascular endothelial growth factor, hepatocyte growth factor